Surgical Management of Trigeminal Neuralgia By Microvascular Decompression - Ayub, Shahid; Ilyas, Muhammad; Ali, Mumtaz (Journal of Postgraduate Medical Institute, 2011)
To find out the results of Micrvascular Decompression for trigeminal Neuralgia, not responding to conservative treatment. Between January 1998 and December 2001, 50 patients underwent Microvascular decompression for trigeminal neuralgia in the department of Neurosurgery HMC, Peshawar. There were 36(72%) male and 14(28%) female patients. Among them 48(96%) were unilateral cases of trigeminal neuralgia. Right side was involved in 18(36%) and left side in 32(64%). All patients underwent Microvascular decompression. Trigeminal neuralgia is diease of different etiologies. Vascular compression of the trigeminal nerve roots at its entry into pons is one of the most accepted aetiology. Microvascular decompression has become one of the primary treatment of trigeminal neuralgia. We believe that in patient where medical treatment fail to respond, microvascular decompression is the treatment of choice in trigeminal neuralgia.